2022
DOI: 10.1073/pnas.2207545119
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain dopamine neurons arbiter OCD-like behavior

Abstract: The neurobiological understanding of obsessive–compulsive disorder (OCD) includes dysregulated frontostriatal circuitry and altered monoamine transmission. Repetitive stereotyped behavior (e.g., grooming), a featured symptom in OCD, has been proposed to be associated with perturbed dopamine (DA) signaling. However, the precise brain circuits participating in DA’s control over this behavioral phenotype remain elusive. Here, we identified that DA neurons in substantia nigra pars compacta (SNc) orchestrate ventro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Other motor dysfunctions such as chorea and dystonia have been hypothesised to involve a failure to inhibit unwanted movements in which dopamine dysregulation could be implicated [ 7 ]. Obsessive compulsive disorder (OCD) is thought to involve hyperactivity in parts of the orbito-frontal cortex, and treatments involving dopamine antagonists have been found to augment the benefits of therapies involving serotonin reuptake inhibitors [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other motor dysfunctions such as chorea and dystonia have been hypothesised to involve a failure to inhibit unwanted movements in which dopamine dysregulation could be implicated [ 7 ]. Obsessive compulsive disorder (OCD) is thought to involve hyperactivity in parts of the orbito-frontal cortex, and treatments involving dopamine antagonists have been found to augment the benefits of therapies involving serotonin reuptake inhibitors [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of animal models have been developed to investigate the neurological bases for these disorders, many of which have explored genetic, developmental, or drug- or lesion-induced alterations to the dopamine system [ 77 , 78 , 79 , 80 , 81 , 82 ]. Animal studies have also directly explored the role of dopamine in regulating action selection and motivated behaviour [ 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…11,57 Moreover, SNc DA neurons regulate obsessive-like behaviors in ventromedial striatum and lateral orbitofrontal cortex projections via dual gating. 117 Lastly, the Vglut2 + DA neurons in the SNl are implied in the innervation of the amygdala, 90 demonstrating their potential role in affective behaviors.…”
Section: Midbrain Da Neurons and Affective Disordersmentioning
confidence: 99%
“…Chronic optogenetic activation of the orbitofrontal cortex (OFC) to VMS connection induces an increase in grooming ( Ahmari et al, 2013 ) while enhancing feed-forward inhibition of fast-spiking striatal interneurons driven by lateral OFC optogenetic activation on hyperactive SPNs rescues compulsive behaviors ( Burguière et al, 2013 ). Another recent paper found that optogenetic inhibition of both dSPN-specific SNc projections to the VMS and SNc projections directly to the lateral OFC prevented excessive grooming ( Xue et al, 2022 ).…”
Section: Cellular and Molecular Mechanisms Of Repetitive Behaviormentioning
confidence: 99%